2013
DOI: 10.1002/cssc.201200717
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Nanowhisker Aerogels

Abstract: Chitin nanowhiskers are structured into mesoporous aerogels by using the same benign process used previously in our group to make cellulose nanowhisker aerogels. The nanowhiskers are sonicated in water to form a hydrogel before solvent-exchange with ethanol and drying under supercritical CO2 (scCO2). Aerogels are prepared with various densities and porosities, relating directly to the initial chitin nanowhisker content. scCO2 drying enables the mesoporous network structure to be retained as well as allowing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 57 publications
5
52
0
Order By: Relevance
“…Further increase of bagasse concentration to 10 % resulted in a coarse and dense upside of aerogel with pore diameter at nano-scale (Fig. 6), suggesting the extensive aggregation of bagasse, which was in (Heath et al 2013) agreement with the results from BET surface area analysis. Figure 7 were SEM images from bottom side and upside of bagasse aerogels at high magnification.…”
Section: Nitrogen Adsorption Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…Further increase of bagasse concentration to 10 % resulted in a coarse and dense upside of aerogel with pore diameter at nano-scale (Fig. 6), suggesting the extensive aggregation of bagasse, which was in (Heath et al 2013) agreement with the results from BET surface area analysis. Figure 7 were SEM images from bottom side and upside of bagasse aerogels at high magnification.…”
Section: Nitrogen Adsorption Analysissupporting
confidence: 86%
“…The similar results were reported in the preparation of cellulose nanowhisker aerogels (Heath and Thielemans 2010). However, the increase of bagasse concentration from 7 to 10 % led to a decrease in BET surface area from 185 to 119 m 2 / g. Because BET surface area describes the area accessible to gas adsorption and is dependent on the extent of aggregation of bagasse (Heath et al 2013), the noticeable decrease of BET surface area suggested the significant bagasse aggregation at bagasse concentration 10 %.…”
Section: Nitrogen Adsorption Analysissupporting
confidence: 83%
“…These diffraction peaks indicated that NGEC aerogels clearly retained the crystalline structure of the NGEC. The results of SEM and XRD confirm that the NGEC gels may be formed by aggregation of the NGEC molecules, possibly induced by crystallization as a coherent bulk . In addition, the intensity of diffraction peaks at 12.98° decreases as increasing initial ethanol ratio (from NGC1 to NGC4).…”
Section: Resultsmentioning
confidence: 57%
“…One of the most widely used solvent systems for chitin is a saturated CaCl 2 ·2H 2 O/methanol solution at elevated temperature [12][13][14][15] Hydrogels were then prepared by dialysis of chitin solutions with a saturated CaCl 2 ·2H 2 O/methanol, which were further converted into porous chitins by lyophilization [16,17]. As another example, a solvent exchange of chitin nanowhisker hydrogels with ethanol, followed by drying with supercritical CO 2 , yielded monolithic porous chitins with continuous substructures of porous channels [18].…”
Section: Introductionmentioning
confidence: 99%